The Pricing of Exchange Rate Risk in the Stock Market - Jorion, Philippe (Journal of Financial and Quantitative Analysis, 1991)
This paper examines the pricing of exchange rate risk in the U.S. stock market, using two factor and multi-factor arbitrage pricing models. Evidence is presented that the relation between stock returns and the value of the dollar differs systematically across industries. The empirical results, however, do not suggest that exchange risk is priced in the stock market. The unconditional risk premium attached to foreign currency exposure appears to be small and never significant. As a result, active hedging policies by financial managers cannot affect the cost of capital, and other reasons must explain why firms decide to hedge.